PENGARUH PELATIHAN DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. BANK RIAU KEPRI CABANG SYARIAH PEKANBARU - Harida, Tengku Rizka; Ibrahim, Restu; ', Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is done at PT. Bank Riau Kepri Cabang Syariah Pekanbaru which is located at Sudirman Street number 377, Pekanbaru. Population in this study there all employees, amounting to 66 people, while the number of samples in this study as many as 66 people. Determination of the numbering samples using census method. While to analyze the data, authors using multiple linear regression method with the help of SPSS version 20.0. Based on F test result is known that the variable training, leadership with the same effect on employee performance at PT. Bank Riau Kepri Cabang Syariah Pekanbaru. Based on t test result is known that the training variable be partial effect on employee performance at PT. Bank Riau Kepri Cabang Syariah Pekanbaru. And leadership variabel be partial effect on employee performance at PT. Bank Riau Kepri Cabang Syariah Pekanbaru. Donations effect of training and leadership contributed 45.90% on employee performance at PT. Bank Riau Kepri Cabang Syariah Pekanbaru. While the remaining 54.10% is influenced by other variabels not examined in this study.Keywords : Training, Leadership, Performance